Pendampingan Melek Media Sosial di Pondok Pesantren Idhotun Nasyi'in - Khoirun Nisa; Nashihin Nashihin; Novelya Aleena Rofani; Nihayatus Sakhiyah; Deny Tri Prasetia; Munawaroh Munawaroh (KERIS : Journal of Community Engagement, 2022)
Social Media is a bridge between the community and related agencies, as a place for exchanging information which will later affect the goals or feedback expected by both parties, because knowledge of social media is an urgency that is very much needed in the current era of the industrial revolution 4.0, where all aspects of the digital twin technology or digital twin technology can create virtual versions of installations, processes and applications that exist in the real world, but this is not supported by the ability of students and female students who tend to be low in the use of technology. This service aims to provide skills and understanding for the students of Idhotun Nasyi'in Islamic Boarding School Sugihwaras Kalitengah to utilize social media as the main guide in processing news and information that aims to advance the Idhotun Nasyi'in Islamic Boarding School as well as a tool to expand the network of introductions about Pondok Idhotun Nasyi'in for the intended target community. This activity uses a contextual approach method, namely providing theoretical material first and followed by sorting out talents and interests belonging to two fields, namely (Layouter and Journalism), followed by training related to these two fields. The results of this activity are the students' understanding of the stages of making online news, able to run from news design, news search, news processing and uploading news to social media independently.